Actor-Directors: The Working Lives of Prison Governors - FAULKNER, HILARY,MARY (2011)
Prison Governors are both actors and directors within the Prison Service. They fulfil key roles at the boundaries of individual prisons and the wider contexts: organisational, social and political, within which prisons function. In this thesis I study aspects of the working lives of nine Governing Governors of public sector prisons in England and Wales from a performative, role-playing perspective. In addition to this I utilise two recently developed models to provide frameworks for examining two key areas of Governors’ roles: those of leadership and of well-being. I use literary collage and imaginative writing to present and interpret interview material together with self interviews and reflection on my experiences as a Ph.D. researcher, enabling me to show how my research developed and how I have developed as a researcher. In concluding my thesis I make a number of recommendations in the areas of leadership learning, well-being, further research and research methodology